2019
DOI: 10.1016/j.redox.2019.101116
|View full text |Cite|
|
Sign up to set email alerts
|

Tumoral NOX4 recruits M2 tumor-associated macrophages via ROS/PI3K signaling-dependent various cytokine production to promote NSCLC growth

Abstract: M2-type tumor-associated macrophages (TAMs) infiltration contributes to cancer malignant progression. However, the mechanisms for controlling recruitment and M2 polarization of macrophages by cancer cells are largely unclear. NADPH oxidase 4 (NOX4) is abundantly expressed in non-small cell lung cancer (NSCLC) and mediates cancer progression. NOXs are in close relation with cancer-related inflammation, nevertheless, whether tumoral NOXs influence microenvironmental macrophages remains undentified. This study fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 37 publications
1
81
0
Order By: Relevance
“…ROS produced by cancer cells stimulates various cytokine production, including CCL7, IL-8, CSF-1 and VEGF-C, that all contribute to enhanced NSCLC cell growth. IHC analysis of clinical specimens confirmed the positive correlation of NOX4 and CD68 or CD206 [253]. ROS accumulation in BMDMs that was reached by ROS inducer, glutathione synthesis inhibitor buthionine sulphoximine (BSO), results in increased expression of programmed death ligand-1 (PD-L1) and production of IL-10, IL-17, IL-4, IL-1b, insulin-like growth factor-binding protein 3 (IGFBP-3), and chemokine (C-X-C motif) ligand 1 (CXCL1) that are associated with an immune-suppressive phenotype of macrophages [271].…”
Section: Role Of Hypoxiamentioning
confidence: 66%
See 1 more Smart Citation
“…ROS produced by cancer cells stimulates various cytokine production, including CCL7, IL-8, CSF-1 and VEGF-C, that all contribute to enhanced NSCLC cell growth. IHC analysis of clinical specimens confirmed the positive correlation of NOX4 and CD68 or CD206 [253]. ROS accumulation in BMDMs that was reached by ROS inducer, glutathione synthesis inhibitor buthionine sulphoximine (BSO), results in increased expression of programmed death ligand-1 (PD-L1) and production of IL-10, IL-17, IL-4, IL-1b, insulin-like growth factor-binding protein 3 (IGFBP-3), and chemokine (C-X-C motif) ligand 1 (CXCL1) that are associated with an immune-suppressive phenotype of macrophages [271].…”
Section: Role Of Hypoxiamentioning
confidence: 66%
“…ROS production is regulated by NADPH oxidases. NADPH oxidase 4 (NOX4)-overexpressed lung cancer cell lines A549 and Calu-1, induced the recruitment of murine M2-like TAMs via the ROS/PI3K signaling-dependent pathway [253]. ROS produced by cancer cells stimulates various cytokine production, including CCL7, IL-8, CSF-1 and VEGF-C, that all contribute to enhanced NSCLC cell growth.…”
Section: Role Of Hypoxiamentioning
confidence: 99%
“…Among them, the expression of NOX4 was signi cantly increased.At the same time, the result of lncRNAs microarray showed that the expression of NOX4, JAK and STAT3 was signi cantly increased in 154 VM-related genes of GBC. As mentioned above, NOX4, as a member of the NADPH oxidase family, plays vital roles in proliferation, metastasis and angiogenesis of tumors through the production of ROS [29,43,44]. Then, we detected NOX4 expression in vitro and in vivo using qRT-PCR, western blot and IHC.…”
Section: Discussionmentioning
confidence: 96%
“…Then, we detected NOX4 expression in vitro and in vivo, and con rmed that NOX4 was not only highly expressed in GCAFs, but also in human GBC tissue and stroma. As mentioned above, NOX4, as a member of the NADPH oxidase family, plays vital roles in proliferation, metastasis and angiogenesis of tumors through the production of ROS [42,44,45]. It has been con rmed that NOX4 is highly expressed in many types of tumor cells such as pancreatic cancer [46], renal cell carcinoma [47] and gastric cancer [48].…”
Section: Discussionmentioning
confidence: 97%